The Investigations of Thermomechanical Properties of Polypropylene Composites - Sylwester Norwiński; Przemysław Postawa; Robert Sachajko; Paweł Palutkiewicz; Tomasz Stachowiak (Advances in Polymer Technology)
The article presents the results of the investigations of isotactic polypropylene composites with the following fillers: flame retardants, glass fiber, glass beads, and talc. The process of preparing composites and test samples is described. The investigations were performed using the DMTA method. The evaluation of thermal effects for the investigated molded parts using special device was also presented. The scope of the research included ten polypropylene composites with different content and type of fillers. These measurements allowed us to determine the influence of the filler type and content on the dynamic mechanical properties of iPP composites. The results will be useful for determining the scope of application of the mentioned materials in various fields of industry in the future.